Universities as Suppliers of Entrepreneurship Education Services. The Cases of The University of Seville and The Academy of Economic Studies in Bucharest - Isidoro Romero; Raluca Mariana Petrescu; Alina Elena Balalia (Iosif) (Amfiteatru Economic Journal, 2011)
The paper advocates the role of universities in the knowledge-based economy as suppliers of entrepreneurship education in order to stimulate the emergence of entrepreneurs among their graduates. The paper presents the University of Seville (US) in Spain and the Academy of Economic Studies (AES) in Bucharest, Romania as two case studies. The first part of the paper describes and compares the offer of entrepreneurship education in both universities. This analysis reveals the increasing interest in introducing and promoting entrepreneurship education since the implementation of the Bologna educational process started. The second part of the paper investigates the entrepreneurial intentions among graduates at both academic institutions. This empirical research is based on two surveys carried out among 93 graduates of the US and 98 graduates of the AES in 2010. Following the hypotheses of Ajzen's Theory of Planned Behaviour, Personal Attitudes towards starting-up and Perceived Behavioural Control -self-efficacy perception- are studied as primary antecedents of the entrepreneurial intention. The analysis reveals the existence of higher entrepreneurial intentions for the AES. This seems to be due to more positive personal attitudes towards entrepreneurship for the graduates at the AES, whereas no significant differences in self-efficacy can be appreciated.
Keywords: L26; I23; 330; entrepreneurial intention; entrepreneurship education; university; entrepreneurship supply; entrepreneurial culture; knowledge-based economy